2016
DOI: 10.1038/nmicrobiol.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells are a replicative niche for entry of Toxoplasma gondii to the central nervous system

Abstract: An important function of the blood–brain barrier is to exclude pathogens from the central nervous system, but some microorganisms benefit from the ability to enter this site. It has been proposed that Toxoplasma gondii can cross biological barriers as a motile extracellular form that uses transcellular or paracellular migration, or by infecting a host cell that then crosses the blood–brain barrier. Unexpectedly, analysis of acutely infected mice revealed significant numbers of free parasites in the blood and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
201
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(205 citation statements)
references
References 43 publications
(47 reference statements)
4
201
0
Order By: Relevance
“…However, in agreement with our findings, transfer of a mixed lymphocyte population (predominantly B cells) did not augment parasite dissemination relative to free tachyzoite controls 36. Our findings are also in agreement with more recent data demonstrating that free tachyzoites are able to cross the blood‐brain barrier without the assistance of host immune cells 8. While this latter study did not exclude the idea that immune cells may facilitate invasion of endothelial cells by bringing parasites in close contact with endothelial cells, our own analysis showed no increase in the presence of NK cells in either the brain or associated vasculature following infection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in agreement with our findings, transfer of a mixed lymphocyte population (predominantly B cells) did not augment parasite dissemination relative to free tachyzoite controls 36. Our findings are also in agreement with more recent data demonstrating that free tachyzoites are able to cross the blood‐brain barrier without the assistance of host immune cells 8. While this latter study did not exclude the idea that immune cells may facilitate invasion of endothelial cells by bringing parasites in close contact with endothelial cells, our own analysis showed no increase in the presence of NK cells in either the brain or associated vasculature following infection.…”
Section: Discussionsupporting
confidence: 93%
“…Splenic NK cells were selected as, upon adoptive transfer, they have been shown to recirculate through all organs ordinarily containing NK cells 31. Previous studies showed that tachyzoites are detected in lymphoid tissues early after infection (between 2 and 6 days),4, 12, 32, 33 while parasites were detected in the brains of infected animals by 7 dpi 4, 8, 30, 34. We therefore decided to evaluate the parasite burden in the spleen and the brain of infected animals by PCR at 4 and 7 dpi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of a powerful immune system and cells specialized in protection against foreign invaders, pathogens have developed clever strategies to cross or circumvent these defences and ultimately access the brain. In this issue of Nature Microbiology, Konradt et al 1 report a new route of entry for the parasite Toxoplasma gondiireplication within and lysis of cerebral endothelial cells. This mechanism of entry into the CNS contrasts with the previously proposed 'Trojan horse' decoy strategy that recruits motile host immune cells 2 and facilitates dissemination.…”
mentioning
confidence: 99%
“…In March, we learned how Toxoplasma gondii accesses the central nervous system through the infection and lysis of endothelial cells in the brain vasculature 3 . Perhaps the most visible study published (and certainly the most read) came in the May issue, with an update to the 'tree of life' from Laura Hug and colleagues, revealing the dominance of bacterial diversity and extensive evolution in some branches of the tree 4 .…”
mentioning
confidence: 99%